State Liability Regimes within the United States and Auditor Reporting - Anantharaman, Divya; Pittman, Jeffrey A.; Wans, Nader (The Accounting Review, 2016)
ABSTRACT We examine how state liability regimes within the United States affect auditor reporting decisions. We exploit variation across state-level common law in two aspects of auditor liability: the extent to which auditors can be held liable by third parties for negligence, and rules for apportioning liability across multiple defendants. We find that auditors are more likely to issue a modified going-concern (GC) report to financially distressed clients from high-liability states than to those from low-liability states. We sharpen inferences using a natural experiment that examines the causal effects of two exogenous shocks to auditor third-party liability standards, which dramatically restricted auditors' liability in New Jersey in 1995 and in California in 1992. Results from difference-in-differences tests imply that auditors' propensity to issue a modified opinion for client firms in New Jersey and California decreases significantly after the decline in auditors' litigation exposure, relative to control firms from other jurisdictions. These findings add to our understanding of how litigation risk affects auditor behavior and highlight an important source of variation in litigation risk within the U.S. that has seldom been studied to date.